Structural, electrical, and multiferroic characteristics of lead-free multiferroic: Bi(Co0.5Ti0.5)O3–BiFeO3 solid solution. Issue 64 (1st November 2018) - Kumar, Nitin; Shukla, Alok; Kumar, Nripesh; Choudhary, R. N. P.; Kumar, Ajeet
Abstract : A solid solution of bismuth cobalt titanate [Bi(Co0.5 Ti0.5 )O3 ] and bismuth ferrite (BiFeO3 ) with a composition Bi(Co0.40 Ti0.40 Fe0.20 )O3 (abbreviated as BCTF80/20) was synthesized via a cost effective solid-state technique. Abstract : A solid solution of bismuth cobalt titanate [Bi(Co0.5 Ti0.5 )O3 ] and bismuth ferrite (BiFeO3 ) with a composition Bi(Co0.40 Ti0.40 Fe0.20 )O3 (abbreviated as BCTF80/20) was synthesized via a cost effective solid-state technique. Phase identification and basic structural symmetry of the samples were determined by analyzing powder X-ray diffraction data. Field emission scanning electron micrograph (FE-SEM) and energy dispersive X-ray (EDX) spectra were analyzed to evaluate the micro-structural aspects (shape and size, distribution of grains) as well as a quantitative evaluation of the sample. The average crystallite (particle) and grain size were found to be ∼30 nm and ∼1–2 micron, respectively. The electrical parameters (dielectric constant, tangent loss, impedance, modulus, and conductivity) of as-synthesized material were obtained in a temperature range of 300 to 773 K and frequency range of 1 kHz and 1000 kHz. The strong correlation of microstructure ( i.e., grains, grain boundary, etc. ) and electrical parameters of this material were observed. The frequency dependence of electrical impedance and modulus exhibited a deviation from an ideal Debye-like relaxation process. The dependence of dielectric relaxation mechanism on frequency and temperature is discussed in detail. The field dependent polarization ( P – E hysteresis loop) of BCTF80/20 exhibited an enhanced value of remnant polarization as compared to that of BiFeO3 (referred as BFO). At room temperature (300 K), the magnetic hysteresis loop measurements also showed a significant improvement in the magnetization of BCTF80/20. Thus, based on these enhanced values of remnant polarization and magnetic parameters, we can assume that BCTF80/20 may be considered as a promising candidate for some new generations of electronic devices.